Pattern recognition of fractal profiles in coagulation-flocculation process of wastewater via neural network - Siti Rozaimah, Sheikh Abdullah; Pasilatun Adawiyah, Ismail; Mohd. Marzuki, Mustafa; Rakmi, Abd. Rahman (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/